Hypothermia reduces glymphatic transportation in traumatic edematous brain assessed by intrathecal dynamic contrast-enhanced MRI - Bai, Yingnan; Yuan, Mingyuan; Mi, Honglan; Zhang, Fengchen; Liu, Xiangyu; Lu, Chen; Bao, Yinghui; Li, Yuehua; Lu, Qing (Frontiers in Neurology, 2022)
The glymphatic system has recently been shown to clear brain extracellular solutes and can be extensively impaired after traumatic brain injury (TBI). Despite hypothermia being identified as a protective method for the injured brain via minimizing the formation of edema in the animal study, little is known about how hypothermia affects the glymphatic system following TBI. We use dynamic contrast-enhanced MRI (DCE-MRI) following cisterna magna infusion with a low molecular weight contrast agent to track glymphatic transport in male Sprague–Dawley rats following TBI with hypothermia treatment and use diffusion-weighted imaging (DWI) sequence to identify edema after TBI and further distinguish between vasogenic and cytotoxic edema. We found that hypothermia could attenuate brain edema as demonstrated by smaller injured lesions and less vasogenic edema in most brain subregions. However, in contrast to reducing cerebral edema, hypothermia exacerbated the reduction of efficiency of glymphatic transportation after TBI. This deterioration of glymphatic drainage was present not only brain-wide but also showed hemispherical asymmetry and regional heterogeneity across the brain, associated with vasogenic edema. Moreover, our data show that both glymphatic transport reduction and vasogenic edema are closely related to reducing perivascular aquaporin-4 (AQP4) expression. The suppression of glymphatic transportation might eliminate the benefits of brain edema reduction induced by hypothermia and provide an alternative pathophysiological factor indicating injury to the brain after TBI. Thus, this study poses a novel emphasis on the potential role of hypothermia in the management of severe TBI.